Hydrogen bond donor-acceptor hybrid silicon dioxide particle, composite proton exchange membrane and preparation method and application of composite proton exchange membrane
By introducing high-density hydrogen bonding to the surface of silica particles and combining with sulfonated polymers to form hydrogen bonding-acceptor hybrid silica particles, the problem of balance of proton exchange membrane performance is solved and proton conduction is achieved The improvement of performance and mechanical stability has built a long-range dense hydrogen bond network, solving the problems of graft polymer chain regulation and interface interaction on the surface of nanofillers.
Patent Information
- Application Number
- CN202411284695.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
AI Technical Summary
The existing proton exchange membranes are difficult to balance between improving proton conduction performance and mechanical stability performance, and the regulation and interface interaction of nanofiller surface graft polymer chains are difficult to accurately control, which limits the performance improvement of multiphase hybrid PEMs.
By introducing high-density hydrogen bonding acceptors on the surface of silica particles, the grafting reaction is carried out by ultrasonic-aeration treatment method to form hydrogen bonding-acceptor hybrid silica particles and polymerize them with sulfonation. The combination of substances forms a composite proton exchange membrane to regulate the hydrogen bond network structure and improve proton conduction and mechanical stability.
The overall performance of the proton exchange membrane has been improved, the conductivity is improved by 41.2%, and the swelling rate is reduced by 69.56%. At the same time, mechanical stability is improved, and a long-range dense hydrogen bond network is built, which is greener, more accurate and efficient than traditional methods.
Smart Images

Figure CN119144052A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of proton exchange membranes, and specifically relates to a hydrogen bond donor-acceptor hybrid silica particle, a composite proton exchange membrane, and a preparation method and application thereof. Background Art
[0002] As a key component of proton exchange membrane water electrolysis device (PEMWE), proton exchange membrane (PEM) mainly plays the role of conducting protons and isolating the anode and cathode, which requires it to have excellent proton conductivity and mechanical stability. However, the current research on proton exchange membranes has a "trade-off" effect in which proton conductivity and mechanical stability are difficult to balance, which limits its efficient application.
[0003] In order to improve the "trade-off" effect, the researchers decided to design the PEM chain structure, that is, to introduce ionic groups that transport protons and rigid groups that provide mechanical stability at the same time. However, this method has the disadvantages of long cycles and complex operations. Compared with the homogeneous chain structure design method, the multiphase hybrid method is more widely used as a method that directly affects the performance of composite PEM through the interface interaction between the two phases. At present, for most PEMs prepared by the multiphase hybrid strategy, inorganic nanofillers of different dimensions are usually randomly distributed or poorly distributed in the ionomer matrix. By modifying the surface of the nanoelement, the water retention rate of the hybrid PEM under low humidity conditions can be improved to improve proton conductivity while improving the interface interaction. However, it is still impossible to achieve precise control of the grafted polymer chains on the surface of the nanofiller. At the same time, there is a lack of external field control means to accurately regulate the interface interaction behavior between the polymer matrix and the filler, which limits the leapfrog improvement of the performance of the multiphase hybrid PEM.
[0004] Recently, the use of physical and chemical effects generated by ultrasound to regulate the interfacial interactions between multiphases has received increasing attention. In terms of acoustic physical effects, the huge shear force generated by the cavitation effect will affect the aggregation state of polymer chains. At present, researchers have applied ultrasound to the study of protein chains, regulating the conformation of protein molecular chains through ultrasound, exposing active sites and improving chain segment activity. Therefore, acoustic physical effects have great potential for regulating interfacial interactions between phases in multiphase systems.
[0005] Although the ultrasonic preparation of hybrid materials has achieved initial success, the density of hydrogen bond receptor grafting on the surface of current nano-hybrid materials is still very limited, which makes it difficult to construct long-range effective proton transport channels, limiting the leapfrog improvement in the performance of composite PEM. Summary of the invention
[0006] The purpose of the present invention is to provide a hydrogen bond donor-acceptor hybrid silica particle, a composite proton exchange membrane, and a preparation method and application thereof. The surface hydrogen bond donor-acceptor density of the hydrogen bond donor-acceptor hybrid silica particle provided by the present invention is relatively high and controllable within a certain range.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] The present invention provides a hydrogen bond donor-acceptor hybrid silica particle, comprising modified silica particles and polyimidazole and polyphenol grafted on the surface of the silica particles; the polyimidazole and polyphenol are connected by hydrogen bonds; the modified silica particles are prepared by modifying silica particles with a silane coupling agent;
[0009] The mass ratio of the modified silicon dioxide particles, polyimidazole and polyphenol is 87.39-94.29:5.71-12.61:3.55-15.72.
[0010] Preferably, the polyimidazole is polyvinylimidazole or polypropyleneimidazole;
[0011] The polyphenol is gallic acid or dopamine;
[0012] The particle size of the silicon dioxide particles is 100-200 nm.
[0013] The present invention also provides a method for preparing the hydrogen bond donor-acceptor hybrid silica particles described in the above technical solution, comprising the following steps:
[0014] The silica particles, the silane coupling agent and the alcohol aqueous solution are mixed and hydrolyzed to obtain modified silica particles;
[0015] The modified silica particles, imidazole monomers and an organic solvent are mixed to carry out a grafting reaction to obtain polyimidazole hybrid silica particles; the grafting reaction is carried out by ultrasound-aeration treatment; the number of ultrasound-aeration treatments is 3 to 24 times;
[0016] The polyimidazole hybrid silica particles are sequentially immersed in a polyphenol solution and ultrasonically treated to obtain the hydrogen bond donor-acceptor hybrid silica particles.
[0017] Preferably, the hydrolysis temperature is 70-75°C and the time is 4-6h;
[0018] The imidazole monomer is vinyl imidazole or 1-allylimidazole; the ultrasonic power of the ultrasonic-aeration treatment is 500-750W, the ultrasonic frequency is 20-25kHz, and the ultrasonic amplitude is 20-40%;
[0019] The soaking temperature is 10-15° C. and the soaking time is 3-4 hours.
[0020] The present invention also provides the use of the hydrogen bond donor-acceptor hybrid silica particles described in the above technical solution or the hydrogen bond donor-acceptor hybrid silica particles obtained by the preparation method described in the above technical solution in a proton exchange membrane.
[0021] The present invention also provides a composite proton exchange membrane, which comprises a sulfonated polymer and hydrogen bond donor-acceptor hybrid silica particles doped in the sulfonated polymer; the hydrogen bond donor-acceptor hybrid silica particles are the hydrogen bond donor-acceptor hybrid silica particles described in the above technical solution or the hydrogen bond donor-acceptor hybrid silica particles obtained by the preparation method described in the above technical solution;
[0022] The mass ratio of the hydrogen bond donor-acceptor hybrid silica particles to the sulfonated polymer is 4.5-10:100.
[0023] Preferably, the sulfonated polymer comprises sulfonated polysulfone or sulfonated polyetheretherketone.
[0024] The present invention also provides a method for preparing the composite proton exchange membrane described in the above technical solution, comprising the following steps:
[0025] The hydrogen bond donor-acceptor hybrid silica particle dispersion and the sulfonated polymer solution are mixed and ultrasonically treated to obtain a film casting solution;
[0026] The casting solution is used to form a membrane to obtain the composite proton exchange membrane.
[0027] Preferably, the power of the ultrasonic treatment is 500-750 W, the frequency is 20-25 kHz, and the amplitude is 20-40%.
[0028] The present invention also provides the use of the composite proton exchange membrane described in the above technical solution or the composite proton exchange membrane obtained by the preparation method described in the above technical solution in a battery or a water electrolysis device.
[0029] The present invention provides a hydrogen bond donor-acceptor hybrid silica particle, comprising modified silica particles and polyimidazole and polyphenol grafted on the surface of the silica particles; the polyimidazole and the polyphenol are connected by hydrogen bonds; the modified silica particles are prepared by modifying silica particles with a silane coupling agent; the mass ratio of the modified silica particles, polyimidazole and polyphenol is 87.39-94.29:5.71-12.61:3.55-15.72. The surface hydrogen bond donor-acceptor hybrid silica particles provided by the present invention have a high density of hydrogen bond donors and acceptors and are controllable within a certain range. When applied to proton exchange membranes, the hydrogen bond network structure can be regulated, thereby regulating the overall proton conduction performance and mechanical stability of the composite proton exchange membrane.
[0030] The preparation method of hydrogen bond donor-acceptor hybrid silica particles provided by the present invention treats silica particles with a silane coupling agent, and the obtained modified nanoparticles can promote the surface cavitation bubble dynamics behavior and thus promote the generation of free radicals. The imidazole monomer is used as the hydrogen bond acceptor unit, and the number of ultrasound-aeration cycles is changed through an aeration-assisted sonochemical method to accurately control the polymerization reaction process of the hydrogen bond acceptor monomer at the surface interface of the inorganic solid nanoparticle, thereby achieving controllable grafting. In addition, a series of organic-inorganic hybrid nano-elements with different surface hydrogen bond donor-acceptor densities are synthesized in combination with polyphenols, which can be used as a stimulus-responsive functional composite material.
[0031] The composite proton exchange membrane provided by the present invention has an electrical conductivity of up to 0.24S / cm, which is 41.2% higher than that of pure SPSF; and a swelling rate of up to 12.52%, which is 69.56% lower than that of pure SPSF.
[0032] The preparation method of the composite proton exchange membrane provided by the present invention generates multiphase interfacial interactions through ultrasonic action, uses organic-inorganic hybrid nano-elements as fillers, and uses sulfonated polymers as ionomer matrix to achieve precise regulation of the three-phase hydrogen bond network structure in the composite proton exchange membrane. This method can achieve performance regulation of the composite proton exchange membrane through the two-phase hydrogen bond network formed by the "ionomer matrix-filler", regulate the overall proton conduction performance and mechanical stability of the composite PEM, improve the "trade-off" effect, and construct a long-range dense hydrogen bond network. Compared with traditional multiphase hybrid composite proton exchange membranes, it is greener, more accurate and more efficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0034] Figure 1 The infrared spectra of SiO2 particles, SiO2 particles modified by silane coupling agent and SiO2@PVI hybrid nanoparticles obtained in Examples 1 to 5;
[0035] Figure 2 The thermogravimetric curves of SiO2 particles, SiO2 particles modified by silane coupling agent and SiO2@PVI hybrid nanoparticles obtained in Examples 1 to 5;
[0036] Figure 3 The infrared spectra of the SPSF proton exchange membrane and the SPSF / GA-SiO2@PVI composite proton exchange membrane prepared in Examples 6 to 10;
[0037] Figure 4 This is a scanning electron microscope image of the SPSF / GA-SiO2@PVI composite proton exchange membrane prepared in Examples 8 to 10. DETAILED DESCRIPTION
[0038] The invention provides a hydrogen bond donor-acceptor hybrid silica particle, comprising modified silica particles and polyimidazole and polyphenol grafted on the surface of the silica particles; the polyimidazole and the polyphenol are connected by hydrogen bonds; the modified silica particles are prepared by modifying silica particles with a silane coupling agent.
[0039] In the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art.
[0040] In the present invention, the mass ratio of the modified silicon dioxide particles, polyimidazole and polyphenol is 87.39-94.29:5.71-12.61:3.55-15.72, preferably 87.39-92:8-12.61:5-12.
[0041] In the present invention, the particle size of the silicon dioxide particles is preferably 100 to 200 nm, more preferably 120 to 180 nm.
[0042] In the present invention, the polyimidazole is preferably polyvinylimidazole or polypropyleneimidazole, more preferably polyvinylimidazole.
[0043] In the present invention, the polyphenol is preferably gallic acid or dopamine, more preferably gallic acid; the role of the polyphenol is to participate in the regulation and construction of the hydrogen bond network as an additional proton donor.
[0044] The hydrogen bond donor-acceptor hybrid silica particles provided by the present invention have a high density of hydrogen bond donors and acceptors on the surface and are controllable within a certain range. When applied to proton exchange membranes, the hydrogen bond network structure can be regulated, thereby regulating the overall proton conduction performance and mechanical stability of the composite proton exchange membrane.
[0045] The present invention also provides a method for preparing the hydrogen bond donor-acceptor hybrid silica particles described in the above technical solution, characterized in that it comprises the following steps:
[0046] The silica particles, the silane coupling agent and the alcohol aqueous solution are mixed and hydrolyzed to obtain modified silica particles;
[0047] The modified silica particles, imidazole monomers and an organic solvent are mixed to carry out a grafting reaction to obtain polyimidazole hybrid silica particles; the grafting reaction is carried out by ultrasound-aeration treatment; the number of ultrasound-aeration treatments is 3 to 24 times;
[0048] The polyimidazole hybrid silica particles are sequentially immersed in a polyphenol solution and ultrasonically treated to obtain the hydrogen bond donor-acceptor hybrid silica particles.
[0049] The invention mixes silicon dioxide particles, a silane coupling agent and an alcohol aqueous solution, and performs hydrolysis to obtain modified silicon dioxide particles.
[0050] In the present invention, the particle size of the silicon dioxide particles is preferably 100 to 200 nm, more preferably 120 to 180 nm; the silicon dioxide particles are preferably prepared by the Stober method.
[0051] In the present invention, the silane coupling agent is preferably γ-methacryloxypropyltrimethoxysilane; the model of the γ-methacryloxypropyltrimethoxysilane is preferably KH570; the mass ratio of the silica particles to the silane coupling agent is preferably 1:1-3, more preferably 1:2-3; the role of the silane coupling agent is to modify the hydroxyl groups on the surface of silica by dehydration condensation, so that the surface of silica has double bonds.
[0052] In the present invention, the alcohol aqueous solution is preferably an ethanol aqueous solution; the volume ratio of ethanol to water in the ethanol aqueous solution is preferably 1:1-2, more preferably 1:1.5-2; the mass ratio of the silica particles to the volume ratio of the alcohol aqueous solution is preferably 1-2g:100-200mL, more preferably 1g-2g:100mL.
[0053] In the present invention, the mixing is preferably: firstly subjecting the silica particles and the alcohol aqueous solution to ultrasonic treatment, and then adding the silane coupling agent; the ultrasonic treatment is preferably carried out in the open; the present invention does not have any special limitation on the process of the ultrasonic treatment, and the method familiar to those skilled in the art can be used.
[0054] In the present invention, the hydrolysis temperature is preferably 70-75° C., more preferably 72-75° C.; the hydrolysis time is preferably 4-6 h, more preferably 4-5 h.
[0055] In the present invention, the hydrolysis preferably further includes freeze-drying; the present invention does not have any special limitation on the freeze-drying process, and the freeze-drying process may be carried out in a manner well known to those skilled in the art.
[0056] After obtaining the modified silica particles, the present invention mixes the modified silica particles, imidazole monomers and an organic solvent to carry out a grafting reaction to obtain polyimidazole hybrid silica particles; the grafting reaction is carried out by ultrasound-aeration treatment.
[0057] In the present invention, the imidazole monomer is preferably vinyl imidazole or 1-allylimidazole, and more preferably vinyl imidazole.
[0058] In the present invention, the mass ratio of the modified silica particles to the imidazole monomer is preferably 1:5-10, more preferably 1:8-10.
[0059] In the present invention, the organic solvent is preferably N,N-dimethylformamide; the volume ratio of the mass of the modified silica particles to the organic solvent is preferably 0.2 g:60-65 mL, more preferably 0.2 g:65 mL.
[0060] In the present invention, the mixture preferably further comprises water; the volume ratio of the organic solvent to water is preferably 10 to 12:1, more preferably 11 to 12:1.
[0061] In the present invention, the ultrasonic mode of the ultrasonic-aeration treatment is inserted ultrasound; the ultrasonic power of the ultrasonic-aeration treatment is preferably 500-750W, more preferably 550-700W; the ultrasonic frequency is preferably 20-25kHz, more preferably 22-25kHz; the ultrasonic amplitude is preferably 20-40%, more preferably 30-40%, and the time is preferably 3-5min, more preferably 3-4min; the ultrasonic-aeration treatment preferably adopts circulating water to control the temperature; the temperature of the circulating water is preferably 4-15°C, more preferably 6-12°C; the aeration time of the ultrasonic-aeration treatment is preferably 1-2min, more preferably 1min; the nitrogen introduction rate is preferably 0.35-0.4L / min, more preferably 0.35L / min; the number of ultrasonic-aeration treatments is preferably 3-24 times, more preferably 6-15 times; GA-SiO2@PVI hybrid nanoparticles with different surface polyimidazole grafting densities are obtained under different ultrasonic-aeration cycle times.
[0062] In the present invention, the ultrasonic-aeration treatment preferably further includes washing and drying; the washing includes N,N-dimethylformamide washing and deionized water washing performed in sequence; the drying is preferably freeze-drying; the present invention does not have any special limitation on the freeze-drying process, and a method familiar to those skilled in the art can be used.
[0063] After obtaining the polyimidazole hybrid silica particles, the present invention sequentially immerses the polyimidazole hybrid silica particles in a polyphenol solution and performs ultrasonic treatment to obtain the hydrogen bond donor-acceptor hybrid silica particles.
[0064] In the present invention, the solvent of the polyphenol solution is preferably dimethyl sulfoxide; the concentration of the polyphenol solution is preferably 0.01-0.2 g / 0.2 mL, more preferably 0.02-0.08 g / 0.2 mL; the volume ratio of the mass of the polyimidazole hybrid silica particles to the polyphenol solution is preferably 0.01-0.04 g:0.1-0.5 mL, more preferably 0.02 g:0.2 mL.
[0065] In the present invention, the soaking temperature is preferably 4 to 15° C., more preferably 6 to 12° C., and the soaking time is preferably 3 to 5 hours, more preferably 3 to 4 hours.
[0066] In the present invention, the ultrasonic treatment method is preferably inserted ultrasound; the power of the ultrasonic treatment is preferably 500-750W, more preferably 550-700W; the frequency is preferably 20-25kHz, more preferably 22-25kHz; the amplitude is preferably 20-40%, more preferably 30-40%; the temperature is preferably room temperature; the time is preferably 20-40min, more preferably 30-40min; the role of the ultrasonic treatment is to regulate the formation of hydrogen bonds.
[0067] In the present invention, the hydrogen bond donor-acceptor hybrid silica particles are preferably a hydrogen bond donor-acceptor hybrid silica particle dispersion.
[0068] The preparation method of hydrogen bond donor-acceptor hybrid silica particles provided by the present invention comprises treating silica particles with a silane coupling agent, and the obtained modified nanoparticles can affect the concentration of sono-induced free radicals, thereby being able to adjust the surface hydrogen bond acceptor grafting density. In addition, imidazole monomers are used as hydrogen bond acceptor units, and the number of ultrasound-aeration cycles is changed through an aeration-assisted sonochemical method to accurately control the polymerization process of hydrogen bond acceptor monomers at the surface interface of inorganic solid nanoparticles, thereby achieving controllable grafting. In addition, a series of organic-inorganic hybrid nano-elements with different surface hydrogen bond donor-acceptor densities are synthesized in combination with polyphenols, which can be used as stimulus-responsive functional composite materials.
[0069] The present invention also provides the use of the hydrogen bond donor-acceptor hybrid silica particles described in the above technical solution or the hydrogen bond donor-acceptor hybrid silica particles obtained by the preparation method described in the above technical solution in a proton exchange membrane.
[0070] The present invention does not have any special limitation on the application process of the hydrogen bond donor-acceptor hybrid silica particles in the proton exchange membrane, and the application process may be carried out in a manner well known to those skilled in the art.
[0071] The present invention also provides a composite proton exchange membrane, which comprises a sulfonated polymer and hydrogen bond donor-acceptor hybrid silica particles doped in the sulfonated polymer; the hydrogen bond donor-acceptor hybrid silica particles are the hydrogen bond donor-acceptor hybrid silica particles described in the above technical solution or the hydrogen bond donor-acceptor hybrid silica particles obtained by the preparation method described in the above technical solution;
[0072] The mass ratio of the hydrogen bond donor-acceptor hybrid silica particles to the sulfonated polymer is 4.5-10:100.
[0073] In the present invention, the sulfonated polymer preferably includes sulfonated polysulfone or sulfonated polyetheretherketone, and more preferably sulfonated polysulfone; the sulfonation degree of the sulfonated polymer is preferably 40-60%, and more preferably 50-60%.
[0074] In the present invention, the mass ratio of the hydrogen bond donor-acceptor hybrid silica particles to the sulfonated polymer is 4.5 to 10:100, preferably 5 to 8:100.
[0075] In the present invention, the thickness of the composite proton exchange membrane is preferably 20±10 μm, more preferably 20±5 μm.
[0076] The composite proton exchange membrane provided by the present invention has an electrical conductivity of up to 0.24S / cm, which is 41.2% higher than that of pure SPSF; and a swelling rate of up to 12.52%, which is 69.56% lower than that of pure SPSF.
[0077] The present invention also provides a method for preparing the composite proton exchange membrane described in the above technical solution, characterized in that it comprises the following steps:
[0078] The hydrogen bond donor-acceptor hybrid silica particle dispersion and the sulfonated polymer solution are mixed and ultrasonically treated to obtain a film casting solution;
[0079] The casting solution is used to form a membrane to obtain the composite proton exchange membrane.
[0080] The invention mixes a hydrogen bond donor-acceptor hybrid silicon dioxide particle dispersion liquid and a sulfonated polymer solution, and performs ultrasonic treatment to obtain a film casting liquid.
[0081] In the present invention, the solvent of the sulfonated polymer solution is preferably dimethyl sulfoxide; the concentration of the sulfonated polymer solution is preferably 0.2-0.3 g / mL, more preferably 0.25-0.3 g / mL; the sulfonated polymer solution is preferably prepared in a vacuum oven; the preparation temperature of the sulfonated polymer solution is preferably 50-70°C, more preferably 60-70°C; the sulfonated polymer solution is preferably acid-leached, washed and dried in sequence before being prepared; the acid-leaching reagent is preferably a sulfuric acid solution; the time is preferably 20-30 hours, more preferably 25-30 hours; the concentration of the sulfuric acid solution is preferably 0.01-0.2 g / mL, more preferably 0.05-0.15 g / mL; the washing reagent is preferably deionized water; the present invention does not have any special restrictions on the washing process, and washing to neutrality can be carried out in a manner well known to those skilled in the art; the present invention does not have any special restrictions on the drying process, and a manner well known to those skilled in the art can be used; the volume ratio of the dispersion to the sulfonated polymer solution is preferably 1:5-10, more preferably 1:6-8.
[0082] In the present invention, the mixing temperature is preferably 25 to 30° C.; the mixing time is preferably 0.5 to 2 h, more preferably 1 to 2 h.
[0083] In the present invention, the ultrasonic treatment is carried out by inserting ultrasound; the power of the ultrasonic treatment is preferably 500-750W, more preferably 550-700W; the frequency is preferably 20-25kHz, more preferably 22-25kHz; the amplitude is preferably 20-40%, more preferably 30-40%; the time is preferably 20-25min; the ultrasonic treatment is preferably carried out in an ice water bath; the role of the ultrasonic treatment is to regulate the interaction between the particles and the sulfonated polymer chains.
[0084] In the present invention, the mass ratio of polyphenol to sulfonated polymer in the casting solution is preferably 5 to 30:100, more preferably 5 to 20:100, and most preferably 10 to 20:100.
[0085] After obtaining the casting solution, the present invention performs membrane making on the casting solution to obtain the composite proton exchange membrane.
[0086] In the present invention, the film forming method is preferably blade coating; the thickness of the blade coating is preferably 100 to 250 μm, more preferably 150 to 200 μm.
[0087] In the present invention, the coating preferably further includes drying; the drying is preferably vacuum drying; the drying temperature is preferably 40-50° C.; the present invention does not have any special limitation on the drying time, and the time known to those skilled in the art can be used to allow the solvent to completely evaporate.
[0088] The preparation method of the composite proton exchange membrane provided by the present invention generates multiphase interfacial interactions through ultrasonic action, uses organic-inorganic hybrid nano-elements as fillers, and uses sulfonated polymers as ionomer matrix to achieve precise regulation of the three-phase hydrogen bond network structure in the composite proton exchange membrane. This method can achieve performance regulation of the composite proton exchange membrane through the two-phase hydrogen bond network formed by the "ionomer matrix-filler", regulate the overall proton conduction performance and mechanical stability of the composite PEM, improve the "trade-off" effect, and construct a long-range dense hydrogen bond network. Compared with traditional multiphase hybrid composite proton exchange membranes, it is greener, more accurate and more efficient.
[0089] The present invention also provides the use of the composite proton exchange membrane described in the above technical solution or the composite proton exchange membrane obtained by the preparation method described in the above technical solution in a battery or a water electrolysis device.
[0090] In the present invention, the battery is preferably a proton exchange membrane fuel cell; the water electrolysis device is preferably a proton exchange membrane water electrolysis hydrogen production device.
[0091] The present invention does not have any special limitation on the application process of the composite proton exchange membrane in a battery or a water electrolysis device, and a method familiar to those skilled in the art may be used.
[0092] In order to further illustrate the present invention, the hydrogen bond donor-acceptor hybrid silica particles, composite proton exchange membrane, and preparation method and application thereof provided by the present invention are described in detail below in conjunction with the accompanying drawings and examples, but they should not be construed as limiting the scope of protection of the present invention.
[0093] Example 1
[0094] Preparation of SiO2@PVI hybrid nanoparticles with controllable surface hydrogen bond acceptor grafting density:
[0095] 1g of SiO2 particles with a particle size of 100nm obtained by the Stober method was placed in a 100mL mixed solution of ethanol and water (the volume ratio of ethanol to water was 1:1), and the particles were completely and evenly dispersed by open ultrasound. 1g of γ-methacryloxypropyltrimethoxysilane (KH570) was added to the obtained dispersion and hydrolyzed at 75°C for 4 hours, and the modified SiO2@KH570 powder was obtained after freeze drying.
[0096] 0.2g SiO2@KH570 nanoparticles and 2g VI monomer were weighed and placed in a 100mL double-layer jacket containing 60mL N,N-dimethylformamide (DMF) and 5mL deionized water. The ultrasonic horn was inserted into the double-layer jacket glass reactor from the rubber cover, and then the rubber tube connected with the aeration stone was inserted into the glass reactor from the rubber cover and connected to the gas flow meter and nitrogen bottle. Another rubber tube was inserted into the rubber cover and the other end was placed in a beaker with water (below the liquid level). The double-layer jacket glass reactor and the circulating water pump were constructed into a closed water circuit as a cooling water circulation device during the entire reaction process. Before the reaction, the aeration stone was inserted below the liquid level of the reaction liquid, and the nitrogen flow rate was 0.35L / min. After 5 minutes of ventilation, the aeration stone was adjusted to be above the liquid level of the reaction liquid. Then, the reaction liquid was subjected to intermittent cyclic ultrasound by the method of ultrasound for 3min (no ventilation)-stop ultrasound for 1min (nitrogen was passed in the reaction liquid) for 3 times of ultrasound-aeration cycle. After the reaction is completed, the centrifugal reaction dispersion is washed twice with DMF and deionized water respectively, and the centrifugal supernatant is collected. The centrifugal product is then freeze-dried to obtain a white powder sample, which is sealed and stored at room temperature. The ultrasonic frequency is 20kHz, the ultrasonic power is 500W, and the amplitude is 40% of the maximum value. The obtained SiO2@PVI hybrid nanoparticles are recorded as SiO2@PVI-3c, in which the mass percentage of PVI is 5.71%.
[0097] 0.02 g of gallic acid (GA) powder was fully dissolved in 0.2 mL of DMSO, and then 0.02 g of SiO2@PVI-3c particles were added to the GA solution, soaked at 15 °C for 4 h, and treated with inserted ultrasound for 30 min to obtain GA-SiO2@PVI hybrid particles.
[0098] Example 2
[0099] GA-SiO2@PVI hybrid nanoparticles were prepared according to the preparation method provided in Example 1, except that the number of ultrasound-aeration treatments was 6. The obtained SiO2@PVI hybrid nanoparticles were recorded as SiO2@PVI-6c.
[0100] Example 3
[0101] GA-SiO2@PVI hybrid nanoparticles were prepared according to the preparation method provided in Example 1, except that the number of ultrasound-aeration treatments was 9. The obtained SiO2@PVI hybrid nanoparticles were recorded as SiO2@PVI-9c.
[0102] Example 4
[0103] GA-SiO2@PVI hybrid nanoparticles were prepared according to the preparation method provided in Example 1, except that the number of ultrasound-aeration treatments was 12. The obtained SiO2@PVI hybrid nanoparticles were denoted as SiO2@PVI-12c, in which the mass percentage of PVI was 12.61%.
[0104] Example 5
[0105] GA-SiO2@PVI hybrid nanoparticles were prepared according to the preparation method provided in Example 1, except that the number of ultrasound-aeration treatments was 24. The obtained SiO2@PVI hybrid nanoparticles were recorded as SiO2@PVI-24c.
[0106] Example 6
[0107] Preparation of SPSF / GA-SiO2@PVI composite PEM with controllable hydrogen bond network density:
[0108] First, 0.4 g of SPSF was added to a 20 mL glass bottle containing 1.3 mL of dimethyl sulfoxide (DMSO) solution, dissolved in a 60 ° C oven for 4 h and stirred for 1 h. The GA-SiO2@PVI hybrid nanoparticle dispersion obtained in Example 4 was mixed with the SPSF solution. The mixed solution was stirred at room temperature for 1 h, and the inserted ultrasonic rod was inserted below the liquid surface of the mixed solution and ultrasonicated for 20 min in an ice water bath. The obtained ultrasonic dispersion was scraped on a glass plate through a 150 μm four-sided preparation device, and placed in a 40 ° C vacuum oven overnight to obtain a 20-25 μm SPSF / GA-SiO2@PVI composite PEM. The ultrasonic frequency was 20 kHz, the ultrasonic power was 500 W, and the amplitude was 20%. The obtained SPSF / GA-SiO2@PVI composite PEM was recorded as S50-G2.5-SiO2@PVI-12c.
[0109] Example 7
[0110] The SPSF / GA-SiO2@PVI composite PEM was prepared according to the preparation method provided in Example 6, except that the amount of GA added was 0.04 g. The obtained SPSF / GA-SiO2@PVI composite PEM was recorded as S50-G5-SiO2@PVI-12c.
[0111] Example 8
[0112] The SPSF / GA-SiO2@PVI composite PEM was prepared according to the preparation method provided in Example 6, except that the amount of GA added was 0.06 g. The obtained SPSF / GA-SiO2@PVI composite PEM was recorded as S50-G7.5-SiO2@PVI-12c.
[0113] Example 9
[0114] The SPSF / GA-SiO2@PVI composite PEM was prepared according to the preparation method provided in Example 6, except that the amount of GA added was 0.08 g. The obtained SPSF / GA-SiO2@PVI composite PEM was recorded as S50-G10-SiO2@PVI-12c.
[0115] Example 10
[0116] The SPSF / GA-SiO2@PVI composite PEM was prepared according to the preparation method provided in Example 6, except that the amount of GA added was 0.12 g. The obtained SPSF / GA-SiO2@PVI composite PEM was recorded as S50-G15-SiO2@PVI-12c.
[0117] Test Example 1
[0118] The SiO2 particles, the SiO2 particles modified by the silane coupling agent and the SiO2@PVI hybrid nanoparticles obtained in Examples 1 to 5 were characterized by infrared spectroscopy as follows:
[0119] Fourier transform infrared spectrometer (FT-IR) was used to conduct qualitative structural analysis and characterization of various particles. First, an appropriate amount of KBr that had been dried and dehydrated at high temperature was taken from an agate mortar, mixed with a small amount of SiO2 nanoparticles, SiO2@KH570 and SiO2@PVI-XC to be tested, and then fully ground into powder. It was then pressed into a transparent, complete sheet by a pressure device. Finally, the KBr sheet was placed in an infrared spectrometer and the KBr sheet was measured at 500-4000cm -1 The infrared absorption peaks of the tested samples are within the range of 1.40 nm. The infrared spectra of SiO2 particles, SiO2 particles modified by silane coupling agent and SiO2@PVI hybrid nanoparticles obtained in Examples 1 to 5 are shown in FIG. Figure 1 .
[0120] Depend on Figure 1 It can be seen that compared with SiO2, SiO2@KH570 has the characteristic absorption peaks of KH570: the stretching vibration peak of C=O is at 1720cm -1 The symmetric stretching vibration peak of CH in -CH2- appears at 2853cm -1 The asymmetric stretching vibration peak of CH in -CH2- is at 2922cm -1 The CH stretching vibration peak appears at 2980cm -1 Compared with SiO2 nanoparticles, the infrared spectra of SiO2@PVI-3C, SiO2@PVI-6C, SiO2@PVI-9C, SiO2@PVI-12C, and SiO2@PVI-24C produced more characteristic absorption peaks of imidazole groups: at 665cm -1 The stretching vibration peak of CN= on the imidazole ring is generated at 1490cm -1 The C=N stretching vibration peak on the imidazole ring can be observed.
[0121] In addition, due to the increase of organic groups on the SiO2 surface, the -1 The CH symmetric stretching vibration peak in -CH2- at 2922 cm -1 The asymmetric stretching vibration peaks of CH in CH2- have increased significantly, which also indirectly verifies that the content of organic groups on the surface of SiO2 nanoparticles has increased significantly after different ultrasound-aeration cycles. The characterization of infrared spectroscopy shows that the imidazole groups have been successfully grafted on the surface of SiO2 nanoparticles.
[0122] Test Example 2
[0123] Thermogravimetric tests were performed on SiO2 particles, SiO2 particles modified by silane coupling agent, and SiO2@PVI hybrid nanoparticles obtained in Examples 1 to 5:
[0124] 20 mg of the particles to be tested were dried at 80°C for 12 hours, and then analyzed using a PE TGA8000 thermal analyzer under N2 protection. The analysis results showed that the temperature rose from room temperature to 800°C at a rate of 10°C / min. We used the following mathematical formula to preliminarily estimate the grafting rate of the hybrid particles:
[0125]
[0126] Where:
[0127] m1 – mass loss of SiO2@PVI hybrid particles in the temperature range of 250–600 °C;
[0128] m2 – the initial mass of the hybrid particles at room temperature.
[0129] The thermogravimetric test results of SiO2 particles, silane coupling agent modified SiO2 particles and SiO2@PVI hybrid nanoparticles obtained in Examples 1 to 5 are as follows: Figure 2 shown.
[0130] Depend on Figure 2 It can be seen that compared with the thermogravimetric curve of SiO2 nanoparticles, the thermogravimetric curve of SiO2@PVI hybrid particles has a more significant mass loss in the temperature range of 150-700℃. The thermal degradation of the grafted polymer on the surface of SiO2 particles is the main cause of this mass loss. The first weight loss occurred in the range of 150-350℃, which was mainly caused by the degradation of the grafted polymer side chain. The second loss occurred at 350-700℃. Unlike the first loss, the second mass loss is likely related to the damage of the grafted polymer main chain.
[0131] Test Example 3
[0132] The SPSF proton exchange membrane and the SPSF / GA-SiO2@PVI composite PEM prepared in Examples 6 to 10 were subjected to infrared spectroscopy testing. The infrared spectra obtained are shown in FIG. Figure 3 shown.
[0133] Depend on Figure 3It can be seen that the infrared absorption peaks of the hydroxyl groups of S50-G2.5-SiO2@PVI-12c, S50-G5-SiO2@PVI-12c, S50-G7.5-SiO2@PVI-12c, and S50-G10-SiO2@PVI-12c all showed a slight red shift compared with SPSF, while S50-G15-SiO2@PVI-12c with excess gallic acid added showed a blue shift, indicating that the obtained SPSF / GA-SiO2@PVI composite PEM has a three-phase hydrogen bond network regulation mechanism, and different types of hydrogen bonds are formed between gallic acid-imidazole and imidazole-sulfonic acid groups. The three-phase hydrogen bond network structure can be regulated by adjusting the concentration of gallic acid.
[0134] Test Example 4
[0135] The SPSF / GA-SiO2@PVI composite PEM prepared in Examples 8 to 10 was subjected to SEM testing, and the obtained SEM images are shown in Figure 4 .
[0136] Depend on Figure 4 It can be seen that the hybrid particles in the cross-sectional view of S50-G10-SiO2@PVI-12c with the largest hydrogen bond network density also have the best dispersion, which can verify that the interface interaction is the strongest.
[0137] Test Example 5
[0138] The conductivity test was performed on the SPSF proton exchange membrane, and the SPSF / GA-SiO2@PVI composite PEM prepared in Example 6, Example 9, and Example 10. Three cut membranes (0.8×1.2 cm) were placed in a homemade Inplane mold and fixed, and then the membrane was placed in a beaker filled with deionized water to test the change of membrane impedance with temperature. The test temperature was 30-90°C, and the membrane was kept at each temperature for 30 minutes before the test began. The calculation formula of proton conductivity is as follows:
[0139]
[0140] Where: σ——proton conductivity of proton exchange membrane (S / cm); R——resistance of proton exchange membrane (Ω); L——length between two electrodes (cm); W——width of proton exchange membrane (cm); D——thickness of proton exchange membrane (cm). The test results are shown in Table 1.
[0141] Table 1 Conductivity test data of SPSF proton exchange membrane, SPSF / GA-SiO2@PVI composite PEM obtained in Example 6, Example 9 and Example 10
[0142]
[0143] As can be seen from Table 1, Example 6, in which less hydrogen bond modifier (gallic acid) is added, has a slightly improved conductivity compared to pure SPSF due to the formation of an additional hydrogen bond network. As the content of the hydrogen bond modifier increases, when it increases to 0.08 g, as shown in Example 9, its conductivity can reach 0.24S / cm, which is 41.1% higher than pure SPSF, and the density of the three-phase hydrogen bond network reaches the maximum. The subsequent continued addition of the hydrogen bond modifier will cause a reduction in hydrogen bonds between the imidazole-sulfonic acid groups, thereby reducing the proton transfer efficiency and causing a decrease in proton conductivity.
[0144] Test Example 6
[0145] The swelling rate of SPSF proton exchange membrane, SPSF / GA-SiO2@PVI composite PEM prepared in Example 6, Example 9 and Example 10 was tested. First, the length of the membrane in a dry state was measured, then the membrane was completely immersed in deionized water at a certain temperature and kept for 30 minutes, and then the length of the membrane after absorbing water was measured. The test temperature range was 30℃-90℃. The calculation test formula is as follows:
[0146]
[0147] Where: L wet ——The length of a fixed side of the proton exchange membrane before hydration (mm); L dry ——The length of a certain fixed side of the proton exchange membrane after hydration (mm).
[0148] Table 2 Swelling rate test data of SPSF proton exchange membrane, SPSF / GA-SiO2@PVI composite PEM obtained in Example 6, Example 9 and Example 10
[0149]
[0150] As can be seen from Table 2, in Example 6, in which less hydrogen bond modifier (gallic acid) is added, the swelling rate is slightly lower than that of pure SPSF due to the formation of an additional hydrogen bond network. As the amount of gallic acid increases, the density of the three-phase hydrogen bond network in the composite PEM is increased, and the maximum is reached when the amount of gallic acid added is 0.08g, at which time the interaction between the interfaces is the largest, so that the mechanical properties of the composite PEM are improved and the swelling rate is greatly reduced. However, as the gallic acid content is further increased, the three-phase hydrogen bond network structure in the composite PEM is affected by competition, and the density is reduced, resulting in a slight decrease in mechanical properties.
[0151] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A hydrogen bond donor-acceptor hybrid silica particle, characterized in that: The invention comprises modified silicon dioxide particles and polyimidazole and polyphenol grafted on the surface of the silicon dioxide particles; the polyimidazole and polyphenol are connected by hydrogen bonds; the modified silicon dioxide particles are prepared by modifying the silicon dioxide particles with a silane coupling agent; The mass ratio of the modified silicon dioxide particles, polyimidazole and polyphenol is 87.39-94.29:5.71-12.61:3.55-15.
72.
2. The hydrogen bond donor-acceptor hybrid silica particles according to claim 1, characterized in that The polyimidazole is polyvinyl imidazole or polypropylene imidazole; The polyphenol is gallic acid or dopamine; The particle size of the silicon dioxide particles is 100 to 200 nm.
3. The method for preparing the hydrogen bond donor-acceptor hybrid silica particles according to claim 1 or 2, characterized in that: The following steps are involved: The silica particles, the silane coupling agent and the alcohol aqueous solution are mixed and hydrolyzed to obtain modified silica particles; The modified silica particles, imidazole monomers and an organic solvent are mixed to carry out a grafting reaction to obtain polyimidazole hybrid silica particles; the grafting reaction is carried out by ultrasound-aeration treatment; the number of ultrasound-aeration treatments is 3 to 24 times; The polyimidazole hybrid silica particles are sequentially immersed in a polyphenol solution and ultrasonically treated to obtain the hydrogen bond donor-acceptor hybrid silica particles.
4. The preparation method according to claim 3, characterized in that: The hydrolysis temperature is 70-75°C and the time is 4-6h; The imidazole monomer is vinyl imidazole or 1-allylimidazole; the ultrasonic power of the ultrasonic-aeration treatment is 500-750W, the ultrasonic frequency is 20-25kHz, and the ultrasonic amplitude is 20-40%; The soaking temperature is 10-15° C. and the soaking time is 3-4 hours.
5. Use of the hydrogen bond donor-acceptor hybrid silica particles according to claim 1 or 2 or the hydrogen bond donor-acceptor hybrid silica particles obtained by the preparation method according to claim 3 or 4 in proton exchange membranes.
6. A composite proton exchange membrane, characterized in that: The composite proton exchange membrane comprises a sulfonated polymer and hydrogen bond donor-acceptor hybrid silica particles doped in the sulfonated polymer; the hydrogen bond donor-acceptor hybrid silica particles are the hydrogen bond donor-acceptor hybrid silica particles according to claim 1 or 2 or the hydrogen bond donor-acceptor hybrid silica particles obtained by the preparation method according to claim 3 or 4; The mass ratio of the hydrogen bond donor-acceptor hybrid silica particles to the sulfonated polymer is 4.5-10:
100.
7. The composite proton exchange membrane according to claim 6, characterized in that: The sulfonated polymer includes sulfonated polysulfone or sulfonated polyetheretherketone.
8. The method for preparing the composite proton exchange membrane according to claim 6 or 7, characterized in that: The following steps are involved: The hydrogen bond donor-acceptor hybrid silica particle dispersion and the sulfonated polymer solution are mixed and ultrasonically treated to obtain a film casting solution; The casting solution is used to form a membrane to obtain the composite proton exchange membrane.
9. The preparation method according to claim 8, characterized in that: The power of the ultrasonic treatment is 500-750W, the frequency is 20-25kHz, and the amplitude is 20-40%.
10. Use of the composite proton exchange membrane according to claim 6 or 7 or the composite proton exchange membrane obtained by the preparation method according to claim 8 or 9 in a battery or a water electrolysis device.
